Bio-logging of marine migratory species in the law of the sea. (January 2015) - Kraska, James; Crespo, Guillermo Ortuño; Johnston, David W.
Abstract: The use of advanced and emerging remote data-collection technologies, and in particular bio-logging of marine migratory species, raises fundamental questions about the scope of authority of coastal states to regulate marine scientific research in the waters under their jurisdiction. Bio-logging involves the attachment of devices to marine animals that collect and transmit data about their movements and aspects of the local marine environment, and is now routinely used by marine scientists to support conservation programs and augment oceanographic data collection. Tagged marine life, including seabirds, marine mammals, sea turtles and pelagic fishes, may interact unpredictably with the territorial seas and exclusive economic zones (EEZs) of numerous coastal states. This article explores the legal implications of bio-logging within the legal regime of marine scientific research in the law of the sea. Although bio-logging is a form of marine scientific research, when it is initiated outside a coastal state׳s jurisdiction it does not later fall within it, even if the tagged animals subsequently enters a coastal state׳s territorial sea or EEZ.